Broken Promises - Christopher R. Barnhill; Brian A. Turner (University of Kansas Libraries, 2013)
The purpose of this study was to examine the impact that increased perceptions psychological contract breach between student-athletes and their coaches have on student-athletes' affective trust in their coaches, cognitive trust in their coaches, and intentions to leave their team. Based on a sample of 248 NCAA Division I and Division II student-athletes, the results reveal that increased perceptions of psychological contract breach significantly lower student-athletes' cognitive trust in their coaches and significantly increases their intentions to leave their team. Higher levels of psychological contract violation acted as a partial mediator on the relationship between psychological contract breach and cognitive trust. Psychological contract violation also acted as a partial mediator on the relationship between psychological breach and intentions to leave. Neither perceptions of psychological contract breach nor psychological contract violation were significantly related to affective trust.